2018
DOI: 10.1587/transinf.2017edp7299
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tests of a Prototype of IMU-Based Closed-Loop Fuzzy Control System for Mobile FES Cycling with Pedaling Wheelchair

Abstract: Rehabilitation training with pedaling wheelchair in combination with functional electrical stimulation (FES) can be effective for decreasing the risk of falling significantly. Automatic adjustment of cycling speed and making a turn without standstill has been desired for practical applications of the training with mobile FES cycling. This study aimed at developing closed-loop control system of cycling speed with the pedaling wheelchair. Considering clinical practical use with no requirement of extensive modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“… 9 FES can enable those with SCI to perform different functional tasks such as grasping, 10 walking, 10 standing, 11 transferring, 7 cycling, 12 and rowing. 13 Because walking and sitting-to-standing accomplished with the use of FES imposes the risk of falling in individuals with SCI, 14 researchers and clinical practitioners have favored FES-evoked cycling as an exercise therapy due to its safety. During FES-evoked cycling, electrical stimulation is applied to the overlying key muscles to provide the force needed to pedal the bike 15 at the correct force-producing crank angle.…”
Section: Introductionmentioning
confidence: 99%
“… 9 FES can enable those with SCI to perform different functional tasks such as grasping, 10 walking, 10 standing, 11 transferring, 7 cycling, 12 and rowing. 13 Because walking and sitting-to-standing accomplished with the use of FES imposes the risk of falling in individuals with SCI, 14 researchers and clinical practitioners have favored FES-evoked cycling as an exercise therapy due to its safety. During FES-evoked cycling, electrical stimulation is applied to the overlying key muscles to provide the force needed to pedal the bike 15 at the correct force-producing crank angle.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a surge of interest in the field of FES for muscle control, attracting attention from control and system engineers. Various advanced control techniques have been explored to address the complex challenges associated with FES, including the control of activities such as standing up [13,14,15], cycling [2,14,15,16], and knee joint movement [1] [7]. While these techniques have shown promise, they come with their own strengths and limitations, and it is essential to critically evaluate their effectiveness and potential shortcomings.…”
Section: Fes Muscle Controlmentioning
confidence: 99%
“…Typically, persons with SCI have weak ankle muscles 23 or no muscle power and do not have the ability to control ankle muscle contractions 24 and movement. During FES-evoked cycling, solid AFOs are often used to limit and control the ankle motion 25 at 90° angle 26 and provide shank stability 19 that restricts leg movements in the sagittal plane 27 . Ferrante et al 28 reported that the calf muscles generate limited knee flexion action due to the presence of solid AFO, which might reduce the maximum power during FES-evoked cycling in these individuals.…”
Section: Introductionmentioning
confidence: 99%